The role of islamic business ethics in shaping the influence of punishment on discipline, performance, and motivation of lecturers and staff in higher education - Saleh, Muhammad; Artiyanto, Artiyanto; Mukmin, Agus; Hidayatullah, A.; Syarifudin, Amir (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to examine the effect of punishment on the discipline, performance, and motivation of lecturers and staff at Universitas Islam Nusantara Al-Azhaar within the framework of Islamic Business Ethics. This research employs a quantitative approach to investigate a specific population of 185 lecturers and staff, who also serve as the research sample. Data were collected using a questionnaire, and the analysis was conducted using Partial Least Squares (PLS), focusing on two main stages: evaluating the Outer Model (measurement model) and the Inner Model (structural model). An associative approach was used to identify the relationships between variables. The study's findings reveal a significant positive effect of punishment on discipline, performance, and motivation. The research indicates that when punishment is applied fairly and in line with the principles of Islamic Business Ethics, it can enhance discipline and foster higher performance and motivation among individuals. However, the study also highlights that the success of punishment as a tool depends on its implementation, emphasizing the need for adherence to ethical and just guidelines. The results provide insights into the critical role of ethical considerations in applying punishment to foster a productive and disciplined organizational environment. The policies of punishment, discipline, performance, and motivation at Universitas Islam Nusantara Al-Azhaar are carefully designed to be truly aligned with Islamic Business Ethics. The study also shows that the contribution of the punishment variable to discipline is 0.606, to performance is 0.719, and to motivation is 0.794, with the remaining 45.8% explained by other variables outside of this study.